Evaluation of Health on the Net seal label and DISCERN as content quality indicators for patients seeking information about thumb sucking habit - Shital Kiran, DP; Bargale, Seema; Pandya, Parth; Bhatt, Kuntal; Barad, Nirav; Shah, Nilay; Venkataraghavan, Karthik; Ramesh, K (Journal of pharmacy & bioallied science, 2015)
The aim of this study was to evaluate the reliability of websites on the thumb sucking habit using DISCERN instrument and Health on the Net (HON) seal code at a single moment in time. An Internet search engine (www.google.com) was used to identify websites comprising information on "thumb sucking habit." Of over 204,000 links for thumb sucking habit, the first 100 were analyzed in detail. After excluding discussion groups, news and video feeds, and removing carbon copy sites, only 36 relevant websites remained, which were then assessed using the DISCERN instrument and HON seal code. Using the 16 questions of DISCERN for assessing the reliability and quality of the consumer information which were scored from 1 to 5, an appropriate index of the quality of the information was generated. All the assessed websites were also checked for presence or absence of HON seal code. The maximum score attainable for an outstanding website is 80. Of the 36 websites that were scored the highest score obtained by one of the websites according to the DISCERN tool was 55 of 80, and the lowest score achieved was 16 of 80. The websites achieving the maximum and minimum score were children.webmd.com and thebehaviorsolution.com, respectively. The HON seal was displayed only in three websites, which were medicinenet.com, righthealth.com, and children.webmd.com. By directing patients to validated websites on the thumb sucking habit, clinicians can ensure patients find appropriate information.